Molecular and Genomic Impact of Large and Small Lateral Dimension Graphene Oxide Sheets on Human Immune Cells from Healthy Donors. Issue 2 (20th December 2015) - Orecchioni, Marco; Jasim, Dhifaf A.; Pescatori, Mario; Manetti, Roberto; Fozza, Claudio; Sgarrella, Francesco; Bedognetti, Davide; Bianco, Alberto; Kostarelos, Kostas; Delogu, Lucia Gemma
Abstract : Graphene oxide (GO) is attracting great interest in biomedical sciences. The impact of GO on immune cells is one fundamental area of study that is often overlooked, but critical in terms of clinical translation. This work investigates the effects of two types of thoroughly characterized GO sheets, different in their lateral dimension, on human peripheral immune cells provided from healthy donors using a wide range of assays. After evaluation of cell viability, the gene expression was analyzed, following GO exposure on 84 genes related to innate and adaptive immune responses. Exposure to GO small sheets was found to have a more significant impact on immune cells compared to GO large sheets, reflected in the upregulation of critical genes implicated in immune responses and the release of cytokines IL1β and TNFα. These findings were further confirmed by whole‐genome microarray analysis of the impact of small GO sheets on T cells and monocytes. Activation in both cell types was underlined by the overexpression of genes such as CXCL10 and receptor CXCR3. Significant energy‐dependent pathway modulation was identified. These findings can potentially pave the foundations for further design of graphene that can be used for immune modulation applications, for example in cancer immunotherapy. Abstract : The possible immunological impact from intented or unintentional exposure to 2D materials is a fundamental area of study in nanomedicine. This work provides an initial comprehensive picture of the immunocompatibility of two different sized graphene oxide sheets using a range of molecular and genomic assays on human immune cells to reveal material structure–immune response function correlations.